2011
DOI: 10.5897/ajbm11.351
|View full text |Cite
|
Sign up to set email alerts
|

How after-sales service quality dimensions affect customer satisfaction

Abstract: School of management, Master of international Marketing management, Islamic azad university-tabriz, Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
3
9
0
1
Order By: Relevance
“…The same result found in hypothesis 4 where P value was also lower than alpha 0.05 which means after-sales service had significant effect on customer loyalty, this supported by the result from previous research which also found that after-sales service had significant effect in improving customer loyalty (Alireza et al, 2011;Kurata & Nam, 2013). PT.…”
Section: After-sales Service On Customer Satisfaction and Customer Losupporting
confidence: 82%
See 2 more Smart Citations
“…The same result found in hypothesis 4 where P value was also lower than alpha 0.05 which means after-sales service had significant effect on customer loyalty, this supported by the result from previous research which also found that after-sales service had significant effect in improving customer loyalty (Alireza et al, 2011;Kurata & Nam, 2013). PT.…”
Section: After-sales Service On Customer Satisfaction and Customer Losupporting
confidence: 82%
“…In this study, the responses of respondents to the research questions given in this study were the highest response is related to the availability of service equipment to facilitate officers to solve problems that occur in products. Through this after-sales service, customers can feel that they are truly valued, because the service is not only provided when they make a purchase, but after the purchase, customers also receive good service, so they feel truly served (Alireza et al, 2011). Table 7 above showed hypothesis 5 was rejected because P value was higher than alpha 0.05, which means customer satisfaction had no effect on customer loyalty.…”
Section: After-sales Service On Customer Satisfaction and Customer Lomentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was indicated that the perceived quality of the product/service is caused by the expectation of customers or clients using the service. Quality is therefore concerned with product longevity and strength, as well as consumer satisfaction in the after-sales service process and through advertisement through word-of-mouth (Alireza, Fatemeh, & Pegah, 2011). This is consistent with research from the OECD (2006) in which quality was defined as the totality of features and characteristics of a product or service that bear on its ability to satisfy stated or implied needs.…”
Section: Service Quality (Servqual)supporting
confidence: 65%
“…However, marketing scholars have not yet agreed upon a generally accepted definition of satisfaction. The term, "after-sales services" is used, to describe services that are provided to the customer after the products have been delivered [1]. The same services are sometimes being also called "field services", when they are embodied in the main characteristics that are located at a customer's site [2].…”
Section: Introductionmentioning
confidence: 99%